Relaxation techniques for people with special needs breaking the barriers - Harrington, Beth; Samdperil, Debra L. ([S.l.] : Samdperil Audio-Visual [production company] ; Research Press [distributor], 1989)
Described a comprehensive relaxation techniques for adults, children, and children with special needs
Narrator: Will Lyman
Keywords: Relaxation -- Technique